Response of fodder cropping sequences to irrigation scheduling in arid environment - PATIDAR, M; RAJORA, M P (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted at Jodhpur during kharif, rabi and summer seasons for three consecutive years (2008-09, 2009-10 and 2010-11) to assess the fodder production potential, water use, water use efficiency and fodder quality of different cropping systems under variable moisture regimes. The main plot treatments consist of four cropping sequences, i.e. bajra–lucerne, cowpea– oat – bajra, Cenchrus ciliaris - C. ciliaris + lucerne, bajra + cowpea (1:1) – oat–sorghum and three irrigation levels, i.e. 50, 75 and 100 mm CPE in subplots with three replications. Among the crop sequences round the year, maximum mean green fodder yield was recorded from cowpea-oat-bajra sequence, which was at par with bajra + cowpea – oat – sorghum sequence but significantly higher than C. ciliaris+lucerne and bajra–lucerne sequences. Similarly, dry matter yield was also maximum from cowpea– oat –bajra sequence which was also at par with C.ciliaris–C. ciliaris+lucerne and bajra + cowpea – oat – sorghum sequences but was only significantly higher than bajra – lucerne sequence. During rabi season all crops produced significantly higher green fodder yield at 50 mm CPE level than 75 and 100 mm CPE levels but dry matter yield was at par at 50 and 75 mm CPE levels. Green and dry matter yields of summer crops were significantly higher at 50 mm CPE level than that of 75 and 100 mm CPE. This showed that irrigation at 75 CPE level optimized dry fodder yield during rabi season and 50 mm CPE during summer season. The fodder yield of C. ciliaris + lucerne system at 50 mm CPE and 75 mm CPE was at par but significantly higher than that of 100 mm CPE while fodder yield of bajra + cowpea (1:1)-oat–sorghum and cowpea –oat–bajra at 50 mm CPE was significantly higher than that of 75 mm CPE. Water use efficiency (WUE) and water productivity were higher with bajra, C. ciliaris and oat grown with sprinkler irrigation. Among cropping sequences• ciliaris -C. ciliaris+ lucerne system had maximum WUE and water productivity but statistically at par with cowpea- oat –bajra sequence. Water use was higher at 50 mm CPE irrigation level but water use efficiency and water productivity were higher with 75 and 100 mm CPE level. Protein yield was maximum with bajra – lucerne system followed by cowpea –oat– bajra while C. ciliaris-C. ciliaris + lucerne system had lowest protein yield being at par with bajra + cowpea–oat–sorghum sequence. Protein yield was higher with 50 mm CPE level as compared to 75 and 100 mm CPE in all cropping sequences. Irrigation at 75 mm CPE was best for C. ciliaris + lucerne intercropping system and 50 mm CPE for bajra + cowpea, oat – bajra, cowpea–oat–sorghum and bajra-lucerne crop sequence for getting higher productivity of quality fodder under arid conditions.